TEACHING STRATEGY - Mariam Mohamed Nor; Rahmad Sukor Ab. Samad; Abdul Halim Ibrahim (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2008)
Educationists hold varying views on the standard of today 's examinations but concur on one issue: Malaysia is producing rote-memorizers which could be behind the better results. They agree that a different approach could result in more intelligent and creative students. The younger generation could be pushed and challenged further by scrapping objective and quantitative questions and replcing them with more open-ended ones. This would allow them to be more creative besides using their intelligence. This study explores teachers' perceptions and practices on the teaching of thinking skills via questioning techniques which was conducted using questionnaires, observations and interviews. Findings showed that the infusion of thinking skills in the teaching and learning is still at the introductory stage and there are still lots of room for improvement.Keywords: education, teaching and learning, thinking skills, and questioning techniques